Ethnology Unboxed: The Making of Culture Through Its Performative (Un)doing - Stambach, Amy (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2018)
This article compares a present-day etsy.com African curio shop — catalogued online and linked to craft-makers in Africa — with the Smithsonian Institution Abbott Collection of ethnological objects from Kilimanjaro, East Africa. The Smithsonian accessioned the Abbott Collection in 1890. A Tanzanian-born Canadian immigrant established the online curio shop circa 2012; she is a descendent of some of the owners of the Abbott collection objects. Building on Butler’s notion of museums without walls (2016) and Martinón-Torres’ concept of chaîne opératoire (2002), this paper argues that the online curio shop, like the Abbott Collection, renders concrete (as in momentarily “still”) a chain of relations of production and exchange that link near and distant places. I deepen this argument by presenting the curio shop owner’s commentary and reflections on the Smithsonian Abbott collection, which she visited recently. The paper concludes with discussion of ethnology’s renewed significance for consumerist and diasporic communities.